Endovascular Fistula Salvage for Preserving Arteriovenous Fistula Failure in Haemodialysis Patient: Tertiary Referral Hospital, a Single-Centre Experience - Karundeng, Billy; Sumangkut, Richard; Tjandra, Djony; Khosama, Yuansun; Juliandi, Tomi (Universitas Sam Ratulangi, 2024)
Abstract: Efficacy of endovascular intervention for the preservation of failing accesses is very important in hemodialysis patients. This study aimed to determine the efficacy of endovascular balloon angioplasty in preserving the patency of hemodialysis arteriovenous fistula (AVF) failure. This was a retrospective study of hemodialysis patients who received endovascular intervention due to access difficulties. A single-center study was created between January 2022 and June 2022. Fistulography was conducted on patients suspected of having access stenosis, and balloon angioplasty was performed in the same setting if stenosis of 50% was confirmed. Post-operative complications and access restenosis or failure were monitored. The results obtained 69 patients with hemodialysis access failure due to AVF stenosis, occlusion, and thrombosis that were admitted or referred to our hospital. The majority of patients were 40-60 years (50.7%); 88.4% patients were male and 11.6% were female, with a mean age of 56.3±11.6 (range, 18–77). The sites of AVF failure were brachiocephalic (81.1%) and radiocephalic (18.9%). There was no complication recorded. The procedure succes rate was 81.1%. In conclusion, endovascular balloon angioplasty is effective in restoring hemodialysis access patency. Recurrence is common, and interventions must be repeated. Keeping access open can save lives. Percutaneous transluminal angioplasty (PTA) can be used to achieve safely and successfully repair arteriovenous fistulas failure. Keywords: angioplasty; arteriovenous fistula; arteriovenous graft; hemodialysis